Microstructure Analysis of Alloy X-750+ for Spacer Grid Application in BWR Reactor Core - Ipin, Mas (My University, 2020)
Due to its durability in hostile environments, nickel-based superalloy X-750 has been used in high temperature (and pressure) applications such as gas turbine, solar thermal power plant, and steam turbine. In nuclear technology, this material is utilized as springs, bolts, and spacer grids in the reactor core. This thesis focuses on the utilization of alloy X-750 as spacer grid in BWR reactor. A previous study showed that a higher iron content of alloy X-750 gives a better corrosion resistance in simulated environment of BWR reactor (5% and 8% wt of Fe content comparison) [7]. Then, a new type of nickel based superalloys was developed by Westinghouse Electric Sweden AB, the so called X-750+ which has dramatically high iron content, i.e. 18%wt. However, corrosion resistant analysis was not performed in this work. Instead, basic microstructure analysis was carried out to give preliminary insight on the physical properties especially in relation to the iron content. Two other samples beside X-750+ were also analyzed as references which are alloy X-750 and 718. All samples were prepared with two type of heat treatments namely the standard heat and two stages heat treatment. The microstructure analysis was divided into two parts, atom probe tomography and Secondary Electron Microscopy (SEM). Samples for atom probe tomography were prepared using electropolishing method to produce needle-shape samples suitable for LEAP 3000 Atom Probe. Meanwhile, SEM analysis was done using JEOL JSM-7800 Prime SEM and LEO Ultra 5.5 SEM. Samples for SEM were polished using grinding paper and liquid diamond complemented by electroetching step to reveal the secondary particles. Results from atom probe measurement were analysed using proxigram, a 2-D particle distribution calculation provided by IVAS software. This analysis suggests that both X-750 and X-750+ differ slightly in term of particle volume fraction which might indicating that the mechanical properties are also similar. Meanwhile, standard heat treatment tends to give a slightly larger volume fraction for alloy X-750 but the opposite fashion was observed for alloy X-750+. Furthermore, heat treatment difference seemed do not affect the particle distribution across the particle interfaces. 1-D analysis was done for alloy 718 since the tertiary particle ( 00) mostly situated side by side with secondary particle ( 0). This analysis showed that both heat treatments did not give any differences. Lastly, SEM analysis revealed the grain boundaries for all samples. Accoriding to SEM analysis, all samples with standard heat treatment revealed more prominent grain boundaries except for alloy 718. However, further investigation should be performed to obtain the chemical compositions across the grain boundaries, such as Transmission Electron Microscopy (TEM) analysis.
Keywords: alloy X-750; microstructure; atom probe tomography; SEM